A Musical Joy - Devendra, Kiran (THE PRIMARY TEACHER, 2006)
Last year, I was travelling from Kolkata to Bolpur. I was excited that I was going to visit Shantiniketan for the first time. It was a wonderful train journey of two hours. The green trees, plants, and small and large water ponds were a sight which was soothing to the eyes. The train stopped for two minutes at a station and hawkers boarded the train. The lemon tea which I had was delicious, I had two cups of it. While I was sipping tea, I saw a man, very thin, very ordinary looking, making a great deal of effort to adjust while resting a very ordinary harmonium on the edge of a seat. Once this effort had been made, he started singing Rabindra Sangeet. It was so soothing. This ordinary, unknown singer was so involved that he only concentrated on giving his best to the passengers. The speed, the moving hawkers, and the loud voices of passengers did not bother him. He was happy that he was giving his best; this happiness was radiating on his thin dark face.